2009
DOI: 10.1161/circoutcomes.108.812859
|View full text |Cite
|
Sign up to set email alerts
|

Stress Reduction Prolongs Life in Women With Coronary Disease

Abstract: Background-Psychosocial stress may increase risk and worsen prognosis of coronary heart disease in women.Interventions that counteract women's psychosocial stress have not previously been presented. This study implemented a stress reduction program for women and investigated its ability to improve survival in women coronary patients. Methods and Results-Two hundred thirty-seven consecutive women patients, aged 75 years or younger, hospitalized for acute myocardial infarction, coronary artery bypass grafting, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
92
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(98 citation statements)
references
References 30 publications
0
92
0
6
Order By: Relevance
“…Patients with a harmonious relationship with a partner may have more social support, healthier habits, better medical adherence, and less psychological stress. Meanwhile, a group‐based stress‐reduction intervention program for women with previous MI or revascularization procedures was associated with improved survival compared with usual care 24. In the general population, the impact of stress on cardiovascular risk factors, specifically high blood pressure, might be mediated by the type of occupation; namely, higher stress levels are associated with high blood pressure in people with low occupational status but with lower blood pressure in those with a higher occupational status 25.…”
Section: Discussionmentioning
confidence: 98%
“…Patients with a harmonious relationship with a partner may have more social support, healthier habits, better medical adherence, and less psychological stress. Meanwhile, a group‐based stress‐reduction intervention program for women with previous MI or revascularization procedures was associated with improved survival compared with usual care 24. In the general population, the impact of stress on cardiovascular risk factors, specifically high blood pressure, might be mediated by the type of occupation; namely, higher stress levels are associated with high blood pressure in people with low occupational status but with lower blood pressure in those with a higher occupational status 25.…”
Section: Discussionmentioning
confidence: 98%
“…251 In addition to the treatment of mood symptoms, there are several other approaches to psychosocial intervention that have proved useful. Two RCTs 252,253 have shown the favourable impact of stress management and social support groups on the prognosis of clinical CAD. Nurse-led interventions reveal beneficial effects on anxiety, depression and general well-being in CAD patients.…”
Section: Joint Esc Guidelinesmentioning
confidence: 99%
“…Some observers have suggested that TABP may have suffered a premature demise given recent evidence showing that interventions targeting TABP have led to improved depression [27], and even improved cardiac endpoints for female CHD patients in particular [28,29]. Aspects of TAPB are also implicitly addressed in interventions such as transcendental meditation (TM) and mindfulness based stress reduction (MBSR) which are sometimes available to patients attending CR [30].…”
Section: Introductionmentioning
confidence: 99%